Kobiety działaczki - ograniczenia i realizacje roli = Women activists - limits and realisations of the role - Radiukiewicz, Anna (Zielona Góra: Lubuskie Towarzystwo Naukowe)
The article presents limits that women have to face when they try to take up active citizenship. The activists of organizations take up roles that are not meant for them. These roles, based on masculine conditions, are defined stereotypically. The results of analysis of individual qualitative interviews with female and male activists of different types of organizations in civil society, as presented in the article, make it possible to observe symptoms of limits that appear in the statements of female respondents.
Keywords: organizacje pozarządowe; obywatelstwo; aktywność obywatelska; kobiety; organizations of civil society; civility; activity of women